Experimental assessment of the 3-axis filament winding machine performance - Quanjin, Ma; M. R. M., Rejab; Kumar, Nallapaneni Manoj; M. S., Idris (Elsevier B.V., 2019)
This paper presents the experimental evaluation method analysis of 3-axis filament winding machine performance. Winding circular test is a sufficient method to evaluate machine performance on winding circular repeatability and winding angle quality. It was concluded that the portable 3-axis filament winding machine had a good winding circular repeatability result, which offered 0.83–1.13 mm winding circular distance with 1.75–3.13% standard deviation. It was provided a good winding angle quality, which relied on 0.35–0.62° difference value with 2.25–8.68% standard deviation. It is indicated that winding circular test and winding angle measurement methods could be used as the experimental assessment to evaluate winding machine or relevant equipment on winding performance and manufacturing capability.